2017
DOI: 10.1186/s13643-017-0514-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of chronic and acute physical activity on working memory performance in healthy participants: a systematic review with meta-analysis of randomized controlled trials

Abstract: BackgroundUnderstanding how physical activity (PA) influences cognitive function in populations with cognitive impairments, such as dementia, is an increasingly studied topic yielding numerous published systematic reviews. In contrast, however, there appears to be less interest in examining associations between PA and cognition in cognitively healthy individuals. Therefore, the objective of this review was to evaluate and synthesize randomized controlled trial (RCT) studies that investigated the effects of bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 69 publications
6
56
1
Order By: Relevance
“…The neurocognitive improvements observed here are consistent with two recently published meta-analyses in healthy humans reporting small but significant effects of chronic exercise on working memory53 and attention and processing speed 52. Notably, both meta-analyses reported that older adults were more likely to show improvement, consistent with normal age-related decline.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The neurocognitive improvements observed here are consistent with two recently published meta-analyses in healthy humans reporting small but significant effects of chronic exercise on working memory53 and attention and processing speed 52. Notably, both meta-analyses reported that older adults were more likely to show improvement, consistent with normal age-related decline.…”
Section: Discussionsupporting
confidence: 91%
“…Further, a recent meta-analysis examining exercise and cognitive function in adults with depression reported no cognitive improvements across aerobic, anaerobic and mind–body interventions (eg, yoga) 59. Indeed, literature reviews reveal considerable variability across studies investigating the impact of exercise on cognitive function outcomes (see Guiney and Machado,60 and Diamond61), possibly related to methodological differences across exercise programmes, clinical and demographic factors of participants, and neurocognitive assessment measures 52 53 59. It is also noteworthy that the vast majority of research on exercise and cognitive functioning has been done in ageing samples, usually to investigate the effects of cognitive decline62; there is little information on the impact of exercise on memory in healthy young and middle-aged adults for comparison purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous meta‐analyses mostly focused on one type of mind‐body exercise, such as tai chi, yoga, or dance, for cognitive functions . Other reviews explored physical exercise including aerobic, resistance exercise, tai chi, or yoga for preventing and addressing cognitive impairment in older adults . Although these reviews involved mind‐body exercise as a component, the studies mainly focused on aerobic and resistance exercise, which might increase the confounding factors and cannot comprehensively and accurately assess the effect of mind‐body exercises on cognitive functions.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10]51 Other reviews explored physical exercise including aerobic, resistance exercise, tai chi, or yoga for preventing and addressing cognitive impairment in older adults. [52][53][54] Although these reviews involved mind-body exercise as a component, the studies mainly focused on aerobic and resistance exercise, which might increase the confounding factors and cannot comprehensively and accurately assess the effect of mind-body exercises on cognitive functions. Therefore, our study paid more attention to the overall effects of mind-body exercise and comprehensively evaluated cognitive performance on cognitive intact and cognitive impairment in older adults, which was different from what was found in previous studies.…”
Section: Findings In Relation To Previous Reviewsmentioning
confidence: 99%
“…It would also be of interest to evaluate open (e.g., badminton) versus closed (walking) skilled exercises on RIF, as recent work suggests that the type of exercise (open vs. closed) may have a unique effect on markers of synaptic plasticity as well as on behavioral measures of executive control [15]. Additionally, recent work suggests that chronic exercise, when compared to acute exercise, may have a greater effect on executive control [40]. Consequently, it would be useful for future work on this paradigm to examine the effects of acute and chronic exercise on RIF.…”
Section: Discussionmentioning
confidence: 99%